Tolfenamic Acid Derivatives: A New Class of Transcriptional Modulators with Potential Therapeutic Applications for Alzheimer’s Disease and Related Disorders - Jaunetta Hill (18255631) (2023)
The field of Alzheimer’s disease (AD) has witnessed recent breakthroughs in the development of disease-modifying biologics and diagnostic markers. While immunotherapeutic interventions have provided much-awaited solutions, nucleic acid-based tools represent other avenues of intervention; however, these approaches are costly and invasive, and they have serious side effects. Previously, we have shown in AD animal models that tolfenamic acid (TA) can lower the expression of AD-related genes and their products and subsequently reduce pathological burden and improve cognition. Using TA as a scaffold and the zinc finger domain of SP1 as a pharmacophore, we developed safer and more potent brain-penetrating analogs that interfere with sequence-specific DNA binding at transcription start sites and predominantly modulate the expression of SP1 target genes. More importantly, the proteome of treated cells displayed ~75% of the downregulated products as SP1 targets. Specific levels of SP1-driven genes and AD biomarkers such as amyloid precursor protein (APP) and Tau proteins were also decreased as part of this targeted systemic response. These small molecules, therefore, offer a viable alternative to achieving desired therapeutic outcomes by interfering with both amyloid and Tau pathways with limited off-target systemic changes. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms242015216